Bosnian girls, art and nationalism - C??voro, Uros??, author. aut Link Link Link
1 online resource.
Keywords: "This book is the first academic study of contemporary Feminist art in Bosnia and Herzegovina (BiH). Focusing on art from BiH - a Former Yugoslav republic that has been largely overlooked in the literature - this book demonstrates the unique contributions by artists in understanding the intersection of gender and class with nationalism in a post-conflict society. Examining the historical precedents and drawing on conversations with the artists, this book examines the way in which artists present a counterpoint to the toxic normative culture of remembrance. It provides an argument for feminist art as a mode of remembrance and anti-nationalist collectivity in a region that has been subject to prolonged instability and crisis. This book will be of interest to scholars in contemporary art, feminist studies, war and conflict studies, and European studies"-- Provided by publisher.